2013
DOI: 10.1007/s10753-013-9779-8
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and Anti-inflammatory Effects of Sanguinarine Solid Lipid Nanoparticles

Abstract: The sanguinarine (SG) was studied for its pharmacokinetic and anti-inflammatory activities with prepared solid lipid nanoparticles (SLNs). The sanguinarine solid lipid nanoparticles (SG-SLNs) were prepared by film-ultrasonic dispersion method and the entrapment efficiency of SG was higher at 75.6 %. The drug release profile of SG was examined in pH 7.4 PBS and 85 % of the SG loaded in SLNs was gradually released during 24 h. We used mice endotoxin shock model which was induced by lipopolysaccharide (1 mg/kg) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Actually, the administration of sanguinarine (10 mg/kg) per os and encapsulated by lipid nanoparticles (SG-SLNs), has been shown to induce an antiinflammatory effect in an LPS-induced endotoxin shock murine model, and the pharmacokinetic studies have proved that the AUC0-24 and Cmax of SG-SLNs were significantly increased when compared to those of sanguinarine alone [109] .…”
Section: Resultsmentioning
confidence: 99%
“…Actually, the administration of sanguinarine (10 mg/kg) per os and encapsulated by lipid nanoparticles (SG-SLNs), has been shown to induce an antiinflammatory effect in an LPS-induced endotoxin shock murine model, and the pharmacokinetic studies have proved that the AUC0-24 and Cmax of SG-SLNs were significantly increased when compared to those of sanguinarine alone [109] .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been reported that SLNs delivery system can enhance the anti-inflammatory activity of SG and protect mice against LPS-induced endotoxic shock [21,31]. Considering the potential of SLNs, the present study focused on the optimization and characterization of SG-loaded SLNs, and compared the effectiveness of free SG and SG-SLNs treatment in the ethanol-induced gastric ulcer model of mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, the research of the drug is hampered by its poor water-solubility. Previously, we investigated the pharmacokinetic and anti-inflammatory activities of SG-SLNs, and the results demonstrated that SG-SLNs have a better solubility as nanodispersion and enhance the anti-inflammatory activity of SG by reducing the levels of pro-inflammatory cytokines TNF-α, IL-6, and NO [21]. Thus, we chose SLNs as a carrier system to improve the solubility of SG.…”
Section: Introductionmentioning
confidence: 99%
“…Schematic representation of Sgr-AuNP and DNA interaction as one of the foremost alkaloids owing to their important contribution in biomedical research. Being a representative of the benzyl isoquinoline alkaloid family, Sgr exhibits numerous important biological activities such as antiinflammatory [17][18] , antioxidant 19 , antifungal 20 , anticancer [21][22][23][24] and antimicrobial [25][26] . Recent studies reveal that Sgr can instigate apoptosis in various cancer cells not only by inducing apoptosis, but it can also exhibit anticancer activity by means of inhibiting telomerase and topo isomerase enzyme activity.…”
Section: Introductionmentioning
confidence: 99%